Enhancing methane yield from crude glycerol anaerobic digestion by coupling with ultrasound or A. niger/E. coli biodegradation - Paulista, Larissa Oliveira (2020)
Anaerobic digestion of crude glycerol from biodiesel production is a feasible way for methane production. However, crude glycerol (CG) contains impurities, such as long-chain fatty acids (LCFA) that can inhibit methanogenic microorganisms. Ultrasound promotes the hydrolysis of LCFA and deagglomerates the microorganisms in biological flocs. Furthermore, Aspergillus niger and Escherichia coli produce lipases capable of degrading LCFA. This study aims at improving the methane yield from anaerobic digestion by coupling with ultrasound or E. coli/A. niger biodegradation. The effect of the different treatments was first assessed in a perfectly mixed batch reactor (PMBR), using diluted CG at concentrations of 0.2%, 1.7%, and 3.2% (v/v). Later, the best conditions were replicated in an upflow anaerobic sludge blanket (UASB) reactor to simulate full-scale practical applications. Experiments in the PMBR showed that ultrasound or A. niger biodegradation steps improved methane yield up to 11% for 0.2% CG and 99% for 1.7% CG, respectively. CG biodegradation by E. coli inhibited the subsequent anaerobic digestion for all concentrations tested. Using a UASB digester, ultrasonic treatment of CG led to an average increase of 29% in methane production. The application of ultrasound led to a lower accumulation of propionic acid in the digested material and increased biogas production. On the other hand, an average 77% increase in methane production was achieved using a preliminary CG biodegradation step by A. niger, when operated at a loading rate of 2.9 kg COD m-3 day-1. Under these conditions, an energy gain of 0.48 kWh day-1, with the production of the 0.434 m3 CH4 kg-1 CODremoval and 0.573 m3 CH4 kg-1 VS, and a biogas quality of 73% in methane were obtained. The digested material was analyzed for the detection and quantification of added-value by-products in order to obtain a broad assessment of the CG valorization through anaerobic digestion. In some experiments, propionic and oxalic acid were detected. However, the accumulation of propionic caused the inhibition of the acetogenic and methanogenic microorganisms.